2016
DOI: 10.1167/iovs.16-19361
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Preconditioning Protects Retinal Photoreceptors: Evidence From a Rat Model of Light-Induced Photoreceptor Degeneration

Abstract: The present study provides evidence, for the first time, that RIP protects photoreceptors against bright light-induced photoreceptor degeneration. This observation is consistent with previous reports of RIP-induced protection of the inner retina and of other vital organs. Brain-derived neurotrophic factor may play a role in mediating the RIP-induced neuroprotection through activation of NGFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 69 publications
1
9
0
2
Order By: Relevance
“…One additional translational note: Determining what minimum magnitude, duration, and frequency of systemic hypoxia are required to induce the heritable, adaptive phenotype we report here is of keen interest to us, but our RHC stimulus is not sacrosanct. Other intermittent systemic hypoxia treatments, 18 remote limb conditioning, 44 , 45 or a pharmacological mimic 46 of either that ultimately modulates the expression of these proteins in a similar manner may someday serve as a viable therapeutic for reducing the incidence of ischemic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…One additional translational note: Determining what minimum magnitude, duration, and frequency of systemic hypoxia are required to induce the heritable, adaptive phenotype we report here is of keen interest to us, but our RHC stimulus is not sacrosanct. Other intermittent systemic hypoxia treatments, 18 remote limb conditioning, 44 , 45 or a pharmacological mimic 46 of either that ultimately modulates the expression of these proteins in a similar manner may someday serve as a viable therapeutic for reducing the incidence of ischemic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models of light-induced retinopathy have been used to study phototoxic retinal damage and associated mechanisms, including oxidative stress responses and metabolic abnormalities [ 31 , 32 , 33 , 34 ]. It was observed that many genes were upregulated in light-damaged retinas of Balb/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…While most animal and clinical studies of RIC have focussed on protection against subsequent severe ischemia-reperfusion injury (e.g. ischemic heart disease, acute pre-renal kidney injury, ischemic stroke), there is evidence from animal studies that the beneficial effects of RIC are not confined to ischemic injuries ( Brandli et al, 2016 ; Liu et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%